Probabilidade de ocorrencia de periodos secos e chuvosos em Rio Claro - SP. - Brino, W. C.; Tavares, A. C. (My University, 1982)
Using the daily rainfall data from 1961 through 1980 the frequency of dry and wet periods was determined. The results of the frequency distribution of dry and wet periods indicated that observed data fit very closely an equation of the type Y = aebn. -after English summary
Probability of occurrence of dry and wet periods at Rio Claro, SP
Keywords: Climate; dry periods; wet periods.